IMPLEMENTASI METODE LEARNING CURVE DALAM PROSES PERAKITAN TAMIYA: ANALISIS EFISIENSI DAN PRODUKTIVITAS - Ridwan Prasetyo; Frans Destri Bintang S; Ega Jerlian; Yossie Saputra; Ifnu Nur Hidayat; Iskandar Zulkarnaen; Hamham Raihan Asworo (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
The purpose of this study is to determine the level of efficiency and productivity in the Tamiya assembly process using the learning curve method. The Learning Curve is a curve that shows the relationship between work experience and work productivity, or a curve that shows a decrease in production costs as a result of increased work experience. The discussion of this research calculates the average time, learning rate, total time, paint, and right and left hand maps in the Tamiya assembly process. In conclusion, the learning curve method is very suitable for measuring a person's productivity in assembling Tamiya and reducing time and costs in the production process.